2008
DOI: 10.1007/s00402-008-0709-4
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary screw fixation in proximal fifth-metatarsal fractures in sports: clinical and biomechanical analysis

Abstract: Introduction and purpose Intramedullary screw Wxation (ISF) of proximal Wfth-metatarsal fractures is known as Wrst treatment option in young, sports active patients. No study analyzed functional and biomechanical outcome before. Hypothetically ISF leads to (1) a high bony union rate within 12 weeks, (2) normal hindfoot eversion strength, and (3) normal gait and plantar pressure distribution. Methods Fourteen out of 22 patients were available for follow-up with an average follow-up of 42 months; clinical and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…5 The described incidence is about 1.8 per 1000 person years. 6 , 7 Aim of the operative fracture treatment is the reduction of nonunion and mal-union rate and a quick return to daily activities or sports in athletes. 8 A recent systematic literature review by Roche on treatment and return to sport following basal fifth metatarsal fractures reveals that acute fractures treated nonoperatively had a lower union rate compared with fractures treated with a intramedullary screw.…”
Section: Discussionmentioning
confidence: 99%
“…5 The described incidence is about 1.8 per 1000 person years. 6 , 7 Aim of the operative fracture treatment is the reduction of nonunion and mal-union rate and a quick return to daily activities or sports in athletes. 8 A recent systematic literature review by Roche on treatment and return to sport following basal fifth metatarsal fractures reveals that acute fractures treated nonoperatively had a lower union rate compared with fractures treated with a intramedullary screw.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]10,13,14,19,[22][23][24]26 Of the 11 published studies reviewed, there were 27 radiographs showing the position of the screw in the fifth MT. [6][7][8]10,13,14,19,[22][23][24]26 Of those 27 radiographs, 78% (21/27) had a screw head that was not fully within the cortex of the fifth MT. Patients with continued pain after fracture union may benefit from appropriate imaging aimed down the lateral tarsometatarsal joints to evaluate for potentially symptomatic hardware or CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature demonstrated (1) a high propensity of radiographs without oblique views clearly showing the tarsometatarsal joints and (2) radiographs that demonstrated screw heads outside the cortex of the fifth MT. 68,10,13,14,19,2224,26 Of the 11 published studies reviewed, there were 27 radiographs showing the position of the screw in the fifth MT. 68,10,13,14,19,2224,26 Of those 27 radiographs, 78% (21/27) had a screw head that was not fully within the cortex of the fifth MT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many have thought most athletes with Jones fractures have a subtle or significant varus hindfoot or lateral foot overload 3,21 due to a subtle varus heel, metatarsus adductus, 50 or plantarflexed first ray. 36 However, our study did not show significant varus in the involved foot.…”
Section: Cavovarus Footmentioning
confidence: 99%